Soybean β-Conglycinin Inhibits Broiler Growth and Nutrient Utilization by Inducing Allergic and Inflammatory Responses, Impairing Intestinal Barrier Integrity and Altering Cecal Microbiota - Yusong Du; Zixi Yu; Shasha Wan; Yunfei Li; Rujie Liu; Jiaxuan Zhang; Zewei Sun; Qingzhen Zhong (Animals, 2025)
This study aimed to comprehensively investigate the impact of soybean β-conglycinin on broiler growth performance, nutrient utilization, allergic and inflammatory responses, intestinal barrier integrity, and cecal microbiota. A total of 168 newly hatched (1-day-old) Arbor Acres broilers with similar body weights were randomly divided into 6 treatment groups with 4 replicates of 7 broilers per replicate: the control group received a soybean-free basal diet, while the remaining five experimental groups were provided with diets supplemented with purified soybean β-conglycinin at the doses of 1%, 2%, 3%, 4%, and 5%. The results demonstrated that dietary 1–5% β-conglycinin supplementation significantly reduced the growth performance, nutrient utilization, and content of digestive enzymes in broilers (p < 0.05). Dietary 1–5% β-conglycinin supplementation also significantly increased the serum levels of histamine, β-conglycinin-specific IgY and IgM, TNF-α, and IL-6 and decreased IL-10 levels; the 3% group had the highest levels of histamine, TNF-α, and IL-6 and the lowest levels of IL-10 (p < 0.05). β-conglycinin supplementation significantly down-regulated the mRNA expression of tight junction proteins, MUC2 and IL-10, and up-regulated the expression of TNF-α and IL-6 in the small intestinal mucosa (p < 0.05). Furthermore, the Shannon and Simpson indices were significantly reduced by dietary 1–5% β-conglycinin administration (p < 0.05). The relative abundance of beneficial bacteria (Blautia, Lactobacillus, and Butyricoccus) was significantly decreased in all treatments (p < 0.05). Taken together, these findings suggest that β-conglycinin induces allergic and inflammatory responses, impairs intestinal barrier integrity, and alters the intestinal microbial balance, ultimately leading to reduced nutrient utilization and inhibited growth in broilers. Notably, our study demonstrated that dietary supplementation with 1% β-conglycinin already had various negative effects on broilers, and particularly supplemental 3% β-conglycinin induced serious allergic and inflammatory reactions. Therefore, in the present study, it is recommended that the inclusion level of β-conglycinin in broiler formula feed should not exceed 1%, i.e., the β-conglycinin content in the diet should not exceed 0.6% (converted from β-conglycinin purification purity).